Over hills and mountains - MESIAS, LADIE; LADIE MESIAS (Naga City A.M.S. Press, 2011)
They encounter harsh weather and breathtaking, treacherous scenery.
Keywords: It emphasizes that while the ascent is physically and mentally demanding, it is the process that builds resilience, character, and wisdom; The metaphorical journey "over hills and mountains" represents life$1 (Bs challenges, personal growth, and the pursuit of goals. s